Structural elucidation and NMR assignments of a new pyrrolizidine alkaloid from Crotalaria vitellina Ker Gawl - Casimiro Bezerra, Denise Aline (Magnetic resonance in chemistry : MRC, 2013)
Copyright © 2013 John Wiley & Sons, Ltd.